A Cross-Sectional Study of Musculoskeletal Health Literacy in Patients With Carpal Tunnel Syndrome. (September 2016) - Rosenbaum, Andrew J.; Dunkman, Andrew; Goldberg, Daniel; Uhl, Richard L.; Mulligan, Michael
Background: Approximately 33% of Americans have inadequate health literacy, which is associated with infrequent use of preventative services, increased hospitalization and use of emergency care, and worse control of chronic diseases. In this study, the Literacy in Musculoskeletal Problems (LiMP) questionnaire was used to evaluate the prevalence of limited musculoskeletal literacy in patients undergoing carpal tunnel release (CTR), as these individuals may be at increased risk of inferior outcomes.Methods: This cross-sectional study included individuals older than or equal to 18 years of age who were scheduled for elective CTR. Participants completed a demographic survey and the LiMP questionnaire during their preoperative office visit. The prevalence of limited health literacy was determined, with chi-square analysis used to determine the influence of demographic parameters.Results: The mean LiMP score was 6 ± 1.40. Limited musculoskeletal literacy was seen in 34% of participants (22/65). Analysis identified race (Caucasian), gender (female), higher education levels (≥college), current or prior employment in a health care field, and a prior physician visit for a non–carpal tunnel musculoskeletal complaint as being associated with higher literacy rates.Conclusions: Approximately one-third of patients scheduled for elective CTR have limited musculoskeletal literacy and may lack the necessary skills required for making informed decisions regarding their care. This is concerning, as CTR is performed in the United States on roughly 500 000 individuals annually, at an estimated cost of 2 billion dollars. The identification of those most at risk is thus crucial, and will facilitate the development of education campaigns and interventions geared toward those who are most vulnerable.